On the Research Path, Application and Reappraisal of the Figurism - ZHAO, Huili (Journal of Research for Christianity in China (JRCC), 2025)
From the end of the 17th century to the beginning of the 18th century, the Figurists represented by Joachim Bouvet (Bai Jin) reinterpreted Chinese traditional classics with Christian thought, and interpreted Christianity with Chinese traditional classics, thus establishing the connection between the two, which was the early attempt of the interpretation of scripture. His ideas have been criticized in both traditions and have been questioned and neglected for a long time. However, their studies do have positive significance, such as gaining a certain legal basis for the spread of Catholicism, objectively promoting the study of Sinology in Europe, and making obvious contributions to the cultural exchanges between China and the West. In the process of modern communication between Chinese tradition and Christian tradition, the ideas and research path of Figurists have always had an influence. This paper selects a few of them to illustrate. During the period of the Republic of China, Canadian missionary Ming Yishi adopted the analysis method of Chinese character glyph, and studied inscriptions on bone inscriptions from the perspective of religious teaching. Wei yisa, the second generation leader of the True Jesus Church, which was founded in 1917, adopted the idea of number concealment to construct the doctrine and interpret the classics, which once again triggered the judgment and reflection on the number concealment method. Professor Tian Tongxin of Jinling Union Theological Seminary conducted a study on the Book of Yijing and the Bible, which is a further expansion of the study of the Figurists. This paper attempts to discuss the research path and influence of the chingists, and tries to make a more objective evaluation, hoping to arouse interest in its critical inheritance, and bring new inspiration to the study of the Sinicization of Christianity.
Keywords: Confluence of Christianity and Confucianism, A Comparative Study of the Bible and the I Ching, Heaven Revelation of Chinese Characters